Analisis Fitur dan Convolutional Neural Network pada Pengenalan Aksen Ucapan - Dwi Sari Widyowaty (Universitas Teknologi Mataram, 2021)
Each country has its characteristics and culture, one of these characteristics is the accent of speech. By listening to someone's accent, we can identify the country of origin of the speaker. Research on accent recognition includes Automatic Speech Recognition (ASR) Technology which is currently being developed, an example of ASR technology, namely Virtual Assistant, the development of this research can be more intelligent Virtual Assistant because it can provide an accent from a speaker. In this study, the authors tried to classify accents from various countries (5 classes), namely English, Spanish, Mandarin, French and Arabic. The dataset used in this study consists of English 627 audio, Spanish 220 audio, Mandarin 132 audio, French 80 audio, and Arabic 172 audio, where all sentences are the same sentence in English. In this study, the audio features used are Mel - Frequency Cepstral Coefficients (MFCC), Zero Crossing Rate (ZCR), and Energy (in librosa it is called RMS). Audio feature extraction generates an array of each audio, the result of audio feature extraction will be the Convolutional Neural Network (CNN) Method input for classifying the accent. This research resulted in 51.30% accuracy for the MFCC feature, 48.05% for the ZCR feature, and 51.95% for the Energy feature. The Energy feature gets good accuracy, followed by the MFCC and ZCR features.